Structural Performances of Reinforced Alkali-Activated Slag Fiber Composite Walls - Hyeon-Jin Lim; Chang-Geun Cho; Sun-Ju Lee; Joo-Won Kang (International Journal of Concrete Structures and Materials)
Abstract To reduce carbon emissions in the construction industry, this study attempted to manufacture alkali-activated slag fiber composites (ASFC) without using cement. Synthetic fibers were incorporated into the alkali-activated slag (AAS) binder, and the mechanical properties of ASFC were evaluated through tests on fresh mixture, compressive strength, and direct tensile behavior. The fresh ASFC showed excellent workability with sufficient slump flow, and its 28-day compressive strength averaged 33.7 MPa. In tensile behavior, ASFC exhibited a strain-hardening response with multiple microcracks, similar to cement-based SHCC, with an ultimate tensile strain of approximately 3–5%. Compared with SHCC, ASFC showed slightly lower first cracking stress and tensile strength, but higher ductility. To assess structural performance, reinforced ASFC wall specimens were tested under in-plane lateral loads and compared with conventional RC and SHCC walls. Reinforcing bars were arranged according to both standard design and minimum reinforcement ratios. ASFC walls showed up to 81.9% and 80.6% higher load capacities than RC walls under standard and minimum reinforcement, respectively. Although RC walls failed due to localized cracks, ASFC walls formed widely distributed microcracks controlled by fiber bridging, improving ductility and delaying failure. These results demonstrate that ASFC, without cement, exhibits compressive strength comparable to concrete and superior tensile ductility. Its application in structural walls can enhance resistance to bending and shear cracks while improving overall load-bearing capacity, making it a promising sustainable material.